An Exploratory Study on the Evaluation of eHealth Interventions in Uganda: Practices, Challenges and Insights - Nabukenya, Josephine; Ashaba, Justus (My University, 2020)
The application of information and communication technology is becoming more popular in healthcare management evidencing improvement of effectiveness, access, quality, and efficiency of the healthcare systems. With increased investment and implementation of eHealth across the world, there is a need to evidence its value. That is, its evaluation is required in order to get the most benefits out of them. To this end, this research study investigates the practices, challenges, and insights regarding the evaluation of eHealth implementations in Uganda.A qualitative approach was employed to conduct the study investigation with key eHealth implementers in Uganda considered as respondents to establish an understanding of their perspectives with respect to ehealth evaluation practices and challenges faced, as well as to derive insights from these perspectives in relation to the World Health Organization (WHO) understanding of digital health evaluation. Results show that Uganda has implemented various eHealth initiatives; however less to none evaluation is undertaken, as it is not a key activity with most of the eHealth implementers. The focus is put on monitoring the ehealth initiatives’ functionality and adoption rather than their outcome and impact.Accordingly, the study recommends the need for an evaluation framework following the WHO global digital health evaluation framework guidelines to elucidate the notion of evaluation, its characteristics, and measurement indicators regards the outcome and impact of ehealth implementations in healthcare and service delivery for Uganda’s health system.
Keywords: eHealth Implementations; Evaluation; Healthcare